Eating disorders : when food turns against you - Sonder, Ben, 1954- (New York : F. Watts, 1993)
Examines such eating disorders as bulimia and anorexia nervosa and discusses possible causes and available treatment.
Includes bibliographical references and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
7-9
Young Adult
Keywords: Eating disorders -- Juvenile literature; Eating disorders; Eating disorders